2018
DOI: 10.1002/hpm.2485
|View full text |Cite
|
Sign up to set email alerts
|

Why do people become health workers?Analysis from life histories in 4 post‐conflict and post‐crisis countries

Abstract: SummaryWhile there is a growing body of literature on how to attract and retain health workers once they are trained, there is much less published on what motivates people to train as health professions in the first place in low‐ and middle‐income countries and what difference this makes to later retention. In this article, we examine patterns in expressed motivation to join the profession across different cadres, based on 103 life history interviews conducted in northern Uganda, Sierra Leone, Cambodia, and Zi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 13 publications
(24 reference statements)
1
22
0
Order By: Relevance
“…Working conditions of healthcare workers in conflict settings were assessed in 21 (45%) studies. Among the articles that discussed sex/gender as a factor in shaping the work experiences of HCWs, eight studies found that females predominate low-paying positions, including nursing, midwifery and community health workers (CHWs), as well as other unpaid positions, while male workers predominate managerial and policy-maker positions [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. These studies attributed the difference in the allocation of job positions to gendered power relations, norms, and stereotypes, such that females are more likely to take on CHW jobs due to limited job opportunities and societal biases that see women only in care-giving roles [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Working conditions of healthcare workers in conflict settings were assessed in 21 (45%) studies. Among the articles that discussed sex/gender as a factor in shaping the work experiences of HCWs, eight studies found that females predominate low-paying positions, including nursing, midwifery and community health workers (CHWs), as well as other unpaid positions, while male workers predominate managerial and policy-maker positions [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. These studies attributed the difference in the allocation of job positions to gendered power relations, norms, and stereotypes, such that females are more likely to take on CHW jobs due to limited job opportunities and societal biases that see women only in care-giving roles [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, studies reported that females are underrepresented in managerial positions due to lower educational levels attained, and difficulties in accessing professional training and development, as well as additional hindrances in promotion that males do not face [ 36 , 37 , 41 ]. Despite these differences, two studies found that both male and female HCWs commonly reported the escape from poverty, higher salaries, personal calling, status, and a sense of deservingness as motivations for joining the profession [ 39 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations